Post-Implant Global Longitudinal Strain as a Predictor of Pacing-Induced Cardiomyopathy in Patients with Preserved Ejection Fraction Undergoing Pacemaker Placement - Sung Soo Kim; Hyung Wook Park; Hyung Ki Jeong (Reviews in Cardiovascular Medicine)
Background: Right ventricular (RV) pacing exacerbates heart failure and increases cardiac mortality in patients with reduced ejection fraction (EF). However, its impact on left ventricular dysfunction in patients with preserved EF remains inconclusive. This study investigates the relationship between RV pacing, global longitudinal strain (GLS), and EF in patients with preserved EF. Methods: This prospective registry study included patients with preserved EF (≥50%) undergoing de novo permanent pacemaker (PPM) implantation for atrioventricular block at Chosun University Hospital, South Korea, from 2018 to 2022. Echocardiographic evaluations were performed pre-implant, post-implant, and at 12 months, with follow-up visits every 3–6 months. Composite outcomes included cardiac death, heart failure hospitalization, pacing-induced cardiomyopathy (PICM), and biventricular pacing (BVP) upgrade. Results: A total of 71 patients (28 males, mean age 73.1 years) were included. Following PPM implantation, significant declines in both EF and GLS were noted, especially in those with PICM. Over three years, 2 patients died, 6 were hospitalized, 7 developed PICM, and 3 underwent a BVP upgrade. Reduced post-implant GLS was an independent predictor of PICM (hazard ratios (HR) 1.715, 95% CI 1.174–2.504; p = 0.005). Receiver operating characteristic (ROC) analysis showed an area under curve (AUC) of 0.92 for GLS, with a GLS <–15.0 having 100% sensitivity and 80.9% specificity for predicting PICM. Conclusions: Post-implant GLS is a reliable predictor of PICM in patients with preserved EF. Regular GLS monitoring can guide timely interventions, including guideline-directed medical therapy or BVP upgrades, to prevent deterioration and improve outcomes.